2012
DOI: 10.1523/jneurosci.3087-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Subsecond Dopamine Release in the Nucleus Accumbens Predicts Conditioned Punishment and Its Successful Avoidance

Abstract: The mesolimbic dopamine system is believed to be a pathway that processes rewarding information. While previous studies have also implicated a general role for dopamine in punishment and its avoidance, the precise nature of subsecond dopamine release during these phenomena remains unknown. Here, we used fast-scan cyclic voltammetry to investigate whether subsecond dopamine release events in the nucleus accumbens encode cues predicting the avoidance of punishment during behavior maintained in a signaled footsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
282
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(322 citation statements)
references
References 34 publications
36
282
4
Order By: Relevance
“…Discrete aversive stimuli evoke pauses in the firing rate of a clear majority of dopamine neurons (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and suppress phasic dopamine release in the NAc (Badrinarayan et al, 2012;Oleson et al, 2012;Roitman et al, 2008;Wheeler et al, 2011; but also see Anstrom et al, 2009;Brischoux et al, 2009;Budygin et al, 2012;Park et al, 2015 for reported increases in phasic dopamine activity to aversive stimuli under some conditions). However, while discrete stimuli are commonly used to study phasic dopamine responses, the time domain of aversive stimuli can range from discrete to prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete aversive stimuli evoke pauses in the firing rate of a clear majority of dopamine neurons (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and suppress phasic dopamine release in the NAc (Badrinarayan et al, 2012;Oleson et al, 2012;Roitman et al, 2008;Wheeler et al, 2011; but also see Anstrom et al, 2009;Brischoux et al, 2009;Budygin et al, 2012;Park et al, 2015 for reported increases in phasic dopamine activity to aversive stimuli under some conditions). However, while discrete stimuli are commonly used to study phasic dopamine responses, the time domain of aversive stimuli can range from discrete to prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is still unknown which major brain region is responsible for sensitized responses in the CAR. The NAc has been reported to play a central role in the maintenance of avoidance response (McCullough et al 1993;Oleson et al 2012). Intra-NAc injection of APD has also been reported to induce suppression of avoidance in a similar manner to systemic injection of APD (Wadenberg et al 1990b).…”
Section: Chapter 3 a Comparative Examination Of Apd-inducedmentioning
confidence: 99%
“…In adult APD treatment, alterations in DA system may be responsible for sensitized CAR suppression response. Two lines of evidence supporting this theory are: (1) DA neurotransmission in the striatum (Darvas et al 2011) and the NAc (McCullough et al 1993;Oleson et al 2012) plays an important role in the maintenance of CAR and (2) local injection of sulpiride, a D2 antagonist, into the NAc induces suppression of CAR (Wadenberg et al 1990b). Li and colleagues have also suggested that, in adult APD treatment, abnormal D2 receptor function may underlie sensitization-like CAR response.…”
Section: Conditioned Avoidance Response (Car) and Catalepsymentioning
confidence: 99%
See 2 more Smart Citations